Biosolids and Biosolid Ashes as Input for Producing Brick-like Construction Materials - Mozo Moreno, William Ricardo; Gómez, Adrián (TECCIENCIA, 2016)
Wastewater treatment plant biosolids in two states, With No Treatment (WNT) and Ashes (A), were added to ceramic paste for brick manufacturing. The elements were cooked at three different temperatures (950°, 1000° and 1050°C) and the percentages of the content Clay-Biosolid WNT and Clay-Biosolid A, were 0, 5, 10 and 15%. Bricks manufactured with 15% ashes at 950°C were found to have a resistance to compression close to 26 MPa, meeting the Colombian Technical Norm 4205 (NTC) for structural and non-structural masonry of internal use and closing or divisory walls that support their own weight. We carried out a chemical, structural and thermic characterization of the raw materials that were used (clay and biosolid). We also performed a leaching test (TCLP) to evaluate toxicity characteristics to determine the safety values for heavy metals (Cr and Zn) in the biosolid. By meeting the requirements indicated in NTC 4205, we proved that the total percentage of biosolid that can be used as an addition in construction materials such as bricks is at least 15%, representing a substantial positive impact on the environment. These results open the path to the proposal of even larger percentages of ceramic paste replacement.